2021
DOI: 10.1007/s00068-021-01803-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of COVID-19 pandemic on emergency anterior abdominal wall hernia surgery: is it safe to postpone elective hernia surgery in the pandemic?

Abstract: Background The aim of this study was to investigate the effects of the COVID-19 pandemic on emergency anterior abdominal wall hernia surgeries (EAAWHS) by comparing the pandemic period with the control period a year ago and to share our experiences in the pandemic period. Methods This single-center retrospective cohort study included all patients who underwent EAAWHS during the pandemic (from 11 March 2020 to 25 January 2021) and control period (1 year before the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Similar to our research, some published studies found a significant decrease in elective surgical treatment for anterior wall abdominal hernias during the Covid‐19 period, 4 also referring to those complicated or not complicated as a paradoxical effect of the pandemic, 5 or perhaps due to the stay‐at‐home government indications 6 . Moreover, a baseline decrease was reported in the elective scheduled surgeries in early 2020 as the result of governmental counteracts, 7 also with a consequent modification of the selection criteria of patients on the waiting list 8 .…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our research, some published studies found a significant decrease in elective surgical treatment for anterior wall abdominal hernias during the Covid‐19 period, 4 also referring to those complicated or not complicated as a paradoxical effect of the pandemic, 5 or perhaps due to the stay‐at‐home government indications 6 . Moreover, a baseline decrease was reported in the elective scheduled surgeries in early 2020 as the result of governmental counteracts, 7 also with a consequent modification of the selection criteria of patients on the waiting list 8 .…”
Section: Discussionsupporting
confidence: 91%
“…Almost all studies showed that WW delays, but does not remove the need for surgical treatment of inguinal hernia, while the risk of complications in case of watchful waiting WW is low and the risk of chronic pain after hernia surgery remains high. A current consideration is that the COVID-19 pandemic 43 may have increased surgeons' [44][45][46] and patients' 47 interest for WW, as well as the reduced opportunity for elective inguinal hernia repairs performed, 48 providing more future data, but no definitive conclusion can be drawn up to now. authors contributed to the study conception and design.…”
Section: Discussionmentioning
confidence: 99%
“…1 This is especially true since the COVID-19 pandemic, during which benign pathologies fell by the wayside. 4,5 Too many acronyms still exist, with few clear definitions for complications, different methods of management (1-day surgery, outpatient surgery, elective and emergency surgery), too many differences in codifying both the disease and treatment (open, robotic, laparoscopy), too much heterogeneity in national healthcare systems when approaching abdominal wall pathology (insurance healthcare or welfare healthcare) and too many differences between low and high-volume centers or hub and spoke centers. Moreover, considering the increasing marketing of different products, such as meshes, laparoscopic and robotic instruments, it is hard to understand how to navigate this world without defined routes while avoiding confusion and complicating the lives of young colleagues who encounter the disease.…”
Section: To the Editormentioning
confidence: 99%
“…Despite the efforts of various scientific societies dedicated to abdominal wall surgery, too much confusion has remained, and abdominal wall hernia is still sometimes neglected if we compare it with oncological diseases 1. This is especially true since the COVID-19 pandemic, during which benign pathologies fell by the wayside 4,5…”
mentioning
confidence: 99%